Concurrent Identification and Characterization of Protein Structure and Continuous Internal Dynamics with REDCRAFT - Omar, Hanin; Hein, Aaron; Cole, Casey A.; Valafar, Homayoun (Frontiers in Molecular Biosciences, 2022)
Internal dynamics of proteins can play a critical role in the biological function of some proteins. Several well documented instances have been reported such as MBP, DHFR, hTS and DGCR8. Despite the importance of internal dynamics of proteins, there currently are few approaches that allow for meaningful separation of internal dynamics from structural aspects using experimental data. Here we present a computational approach named REDCRAFT that allows for concurrent characterization of protein structure and dynamics. Here, we have subjected DHFR (PDB-ID 1RX2), a 159-residue protein, to a fictitious, mixed mode model of internal dynamics. In this simulation, DHFR was segmented into 7 regions where 4 of them were fixed with respect to each other, 2 regions underwent rigid-body dynamics, and one region experienced uncorrelated and melting event. The two dynamical and rigid-body segments experienced an average orientational modification of 7˚ and 12˚ respectively. Three observable RDC data for backbone were generated from 102 uniformly sampled frames that described the molecular trajectory. Structure calculation of DHFR with REDCRAFT by using traditional Ramachandran restraint produced a structure with 29Å of structural difference measured over the backbone atoms (bb-rmsd) over the entire length of the protein and an average bb-rmsd of more than 4.7Å over each of the dynamical fragments. The same exercise repeated with context-specific dihedral restraints generated by PDBMine produced a structure with bb-rmsd of 21Å over the entire length but with bb-rmsd of less than 3Å fragments wise. Finally, utilization of the Dynamic Profile generated by REDCRAFT allowed for the identification of different dynamical regions of the protein and the recovery of individual fragments with bb-rmsd of less than 1Å. Following fragments recovery, our assembly procedure of domains (larger segments consisting of multiple fragments with a common dynamical profile) correctly assembled the four fragments that are rigid with respect to each other, categorized the two domains that underwent rigid-body dynamics, and identified one dynamical region for which no conserved structure could be defined. In conclusion, our approach was successful in identifying the dynamical domains, recovery of structure where it is meaningful, and relative assembly of the domains when possible.